Analysis of the dispersion of performance indicators for decision making between two fuzzy modeling tools (Research, Society and Development, 2020)
Analyzing data processing methods and ensuring consistent results is hard work for scientists, the fact is that the optimization of a process makes a difference regardless of which area is being worked on. There are tools that consolidate studies like this, one of them is the comparative method using dispersion analysis that was used in this research when working with the School Adventurers application, which is one of the objects of study, with which the inferences agent called Fuzzylite was analyzed. The case study was a good option for the research when analyzing the inference methods modeled in the app and making a comparison with the MatLab® Fuzzy Toolbox, so the objective of the present research is to analyze the two mentioned tools and point out which one had the best performance using the same Fuzzy modeling. Through the dispersion analysis it was possible to identify a better result for the model used in Fuzzylite.